2010
DOI: 10.1016/j.jpsychires.2009.08.007
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of treatment response to fluvoxamine in obsessive–compulsive disorder: An fMRI study

Abstract: Recent neuroimaging studies suggest that the pathophysiology of obsessive-compulsive disorder (OCD) may involve more widely distributed large-scale brain systems, including the parietal, occipital, and cerebellar areas, rather than the conventional orbitofronto-striatal model. We hypothesized that not only orbitofrontal cortex and caudate nucleus activities but also posterior brain regions might be associated with subsequent treatment response to serotonin reuptake inhibitors in OCD. The participants were 17 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
34
2
4

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(43 citation statements)
references
References 55 publications
3
34
2
4
Order By: Relevance
“…Furthermore, we found reduced metabolism in the posterior cingulate cortex, the superior frontal cortex, the supplementary motor cortex, and the inferior parietal cortex, again in agreement with previous findings (11,22,23). In particular, Saxena et al showed an elevated frontal metabolism at baseline in patients with comorbid OCD and major depressive disorder (MD) (22).…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Furthermore, we found reduced metabolism in the posterior cingulate cortex, the superior frontal cortex, the supplementary motor cortex, and the inferior parietal cortex, again in agreement with previous findings (11,22,23). In particular, Saxena et al showed an elevated frontal metabolism at baseline in patients with comorbid OCD and major depressive disorder (MD) (22).…”
Section: Discussionsupporting
confidence: 93%
“…This finding is at odds with previous work on OCD in which the precuneus was hypermetabolic after symptom provocation tests (20,23,33), and a trend toward a positive correlation between baseline metabolism and symptom severity has been shown (34). The precuneus is part of the default network (21).…”
Section: Discussioncontrasting
confidence: 65%
See 2 more Smart Citations
“…It has also been linked to OCD pathophysiology, with patients with OCD having higher regional cerebral blood flow at rest and during presentation of neutral and symptom-related stimuli 50 and increased BOLD signal in response to symptom provocation. [51][52][53] Rotge and colleagues 53 suggested that the left STG activation was related to the anxiety manifestations rather than an engagement of the neural circuitry underlying OCDrelated symptoms. It is thought that cerebral hyperactivity seen in patients with OCD might mediate the formation of improper error detection and contribute to uncontrollable OCD symptoms, such as excessive doubt and compulsive checking.…”
Section: Brain Correlates Of Acute Stress In Women With Ocdmentioning
confidence: 99%